Analysis of the Sam50 translocase of excavate organisms supports evolution of divergent organelles from a common endosymbiotic event - Kay, Christopher J.; Lawler, Karen; Kerr, Ian D. (Portland Press:, 2013)
As free-living organisms the ancestors of mitochondria and plastids encoded complete genomes, proteomes and metabolomes. As these symbionts became organelles all these aspects were reduced – genomes have degenerated with the host nucleus now encoding the most of the remaining endosymbiont proteome, while the metabolic processes of the symbiont have been streamlined to the functions of the emerging organelle. By contrast, the topology of the endosymbiont membrane has been preserved, necessitating the development of complex pathways for membrane insertion and translocation. In this study, we examine the characteristics of the endosymbiont-derived β-barrel insertase Sam501 in the excavate super-group. A candidate is further characterized in Trichomonas vaginalis, an unusual eukaryote possessing degenerate hydrogen-producing mitochondria called hydrogenosomes. This information supports a mitochondriate eukaryotic common ancestor with a similarly evolved β-barrel insertase, which has continued to be conserved in degenerate mitochondria.